A Fractal Analysis of Market Efficiency for Indian Technology Equities - Banerjee, Debasish; Mulligan, Robert F. (Indian Journal of Finance, 2010)
This paper employs five alternative methods for estimating Hurst exponent (1951), fractal dimension, andÂ Mandelbrot-LÃ©vy characteristic exponent (LÃ©vy 1925) to examine the fractal character of three information technology equities, Satyam, Tata Consultancy Services, and Infosys. Fractal structure or long memory in equity prices indicate that traditional statistical and econometric methods are inadequate for analyzing security markets. Findings support the weak form of the efficient market hypothesis (EMH), and the more general multi-fractal model of asset returns (MMAR) of Mandelbrot, Fisher, and Calvet (1997).